2011
DOI: 10.3168/jds.2011-4290
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial to evaluate the efficacy of a 5-day ceftiofur hydrochloride intramammary treatment on nonsevere gram-negative clinical mastitis

Abstract: The objective of this study was to evaluate the efficacy of intramammary treatment with ceftiofur hydrochloride of nonsevere, clinical coliform mastitis. One hundred four cases on 5 farms met the enrollment criteria for the study. Escherichia coli was the most common coliform species identified in milk samples from cows with mild to moderate clinical mastitis, followed by Klebsiella spp. and Enterobacter spp. At enrollment, a milk sample from the affected quarter was taken and used for on-farm culture or submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 38 publications
9
81
3
2
Order By: Relevance
“…Our results are in disagreement with those of Schukken et al 34,. who reported 38% bacteriological cure in non-treated cows and 73% bacteriological cure in treated animals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in disagreement with those of Schukken et al 34,. who reported 38% bacteriological cure in non-treated cows and 73% bacteriological cure in treated animals.…”
Section: Discussioncontrasting
confidence: 99%
“…. Although current guidelines do not recommend the use of intramammary antibiotics for cows diagnosed with Gram-negative mastitis314, improved bacteriological and clinical outcomes have been shown in mastitic cows treated with third-generation cephalosporins compared with other antimicrobials or untreated controls1516. However, the impact of these broad-spectrum antibiotics on the milk microbiota (other than major pathogens) remains unknown.…”
mentioning
confidence: 99%
“…Gram-negative pathogens have become far more common in the etiology of IMI, and some culture-based treatment programs recommend leaving cows with Gram-negative isolates on milk culture untreated. 10 However, a recent investigation 12 found that untreated cows with IMI due to Gram-negative pathogens had lower rates of clinical and microbiological cure and left the herd at a higher rate when compared with cows with IMI of Gram-negative causes treated with IMM antimicrobial therapy.…”
Section: Etiologymentioning
confidence: 97%
“…"Randomized Clinical Trial to Evaluate the Efficacy of a 5-Day Ceftiofur Hydrochloride Intramammary Treatment on Nonsevere Gram-negative Clinical Mastitis" by Schukken and colleagues 12 Case criteria: abnormal milk with or without signs of inflammation in the udder The studies regarding ceftiofur suggest that it is effective in improving cure rates of mastitis when compared with untreated controls and that 8 doses may have more efficacy than 2.…”
Section: Treatment Of Mastitis In Cattlementioning
confidence: 98%
“…Clinical mastitis (CM) is classified as the condition where an animal displays the physical symptoms of mastitis [8] and milk production and quality is also affected [9]. Whilst most studies show limited impact of treatment, Schukken et al [10] reported a significant increase in bacteriological cure after the use of antimicrobials for treating non-severe cases of Klebsiella associated CM. Mastitis adversely affects milk production and generally cows do not regain full production levels post recovery [11], leading to considerable economic losses.…”
Section: Introductionmentioning
confidence: 99%